Minnesota Starvation Experiment Oral History Project records - Minnesota Starvation Experiment. Oral History Project
Oral history transcripts and administrative records pertaining to the Minnesota Starvation Experiment, a clinical study administered by lead investigator Ancel Keys at the University of Minnesota Laboratory of Physiological Hygiene between 1944 and 1945. The study, designed to determine the physiological and psychological effects of severe and prolonged dietary restriction and the effectiveness of dietary rehabilitation strategies, was developed in coordination with the Civilian Public Service (CPS) and the U.S. Bureau of Selective Service and involved the participation of conscientious objectors. Results were utilized in the Allied relief assistance to famine victims in Europe and Asia at the end of World War II. Interviews were conducted with participants including Max M. Kampelman.
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Clinical study performed at the University of Minnesota Laboratory of Physiological Hygiene between 1944 and 1945. Also known as the Minnesota Semi-Starvation Experiment, the Minnesota Starvation-Recovery Experiment, and the Starvation Study.
Collection material in English.
Keywords: Kampelman, Max M., -- 1920-2013 -- Interviews; Keys, Ancel, -- 1904-2004.; United States. -- Bureau of Selective Service; Civilian Public Service; Minnesota Starvation Experiment; University of Minnesota. -- Laboratory of Physiological Hygiene; Conscientious objectors -- United States; Starvation; Starvation -- Experiments; Starvation -- Physiological aspects; Starvation -- Psychological aspects; World War, 1939-1945 -- Civilian relief -- Asia; World War, 1939-1945 -- Civilian relief -- Europe; World War, 1939-1945 -- Conscientious objectors